Audit Committee Effectiveness and Accounting Conservatism Practices: The Case of Manufacturing Companies - Ratieh Widhiastuti; Abdul Rohman; Puji Harto (Universitas Pendidikan Indonesia, 2023)
This study aimed to see how financial distress, conflicts of interest, and litigation risk affected accounting conservatism when an audit committee was present as a moderating variable. The population was manufacturing companies indexed at the Indonesia Stock Exchange (IDX) in 2019-2021. The tool employed descriptive and moderation regression analysis. The findings of this research showed that financial distress, conflicts of interest, and litigation risk had a significant positive effect on accounting conservatism. However, the audit committee could not moderate the impact of financial distress, conflict of interest, and litigation risk on accounting conservatism. Financial distress had a significant positive effect on accounting conservatism. Litigation risk was one of the negative impacts of agency problems in a company. These results supported the agency theory, which explains that lawsuits or litigation risks can occur due to differences in interests between management and investors, creditors, or the government. This research contributes to accounting standard policymaking, particularly in applying the conservatism principle. Based on the occurrences and findings of past investigations, which are still inconsistent, the originality of this study was to see how financial distress, conflicts of interest, and litigation risk affected accounting conservatism by including the audit committee variable as a moderating variable.